HUBUNGAN KECERDASAN MORAL DENGAN SELF REGULATION ANAK DI TK WALDHA AL ISLAMY (WHY) KECAMATAN TAMPAN PEKANBARU - Rafika, Rafika; Risma, Devi; Febrialismanto, Febrialismanto (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract:This study background due to the persitence of low moral intelligence in children. Moral Intelligence has an important role in determining one’s behavior. A good moral intelligence will have a positive impact on the development of children’s sel-regulation. Without being supported by an self regulation, then the children will encounter difficulties in achieving something to its full potential and they will a find it difficult to de succed.The aim of this research is to know determine the corellation of moral intelligence to the self-regulation of children in kindergarten WHY at Tampan District of Pekanbaru. The population of this research is kindergarten’ s teachers at Tampan District of Pekanbaru that consists of 80 children, the samples of this research are 80 childrens which taken by using saturated sampling tecnique. Method of this research is Pearson Product Moment correlation to know the corellation between moral variables with self-regulation of children. In this researh data technique used by uising chek list. The technique of analyzing data used scale test and statistic analytical by using SPSS program for Windows Ver.7. Based on hypothesis there is any significant positive corellation between moral intelligence with self-regulation of children in kindergarten WHY at Tampan District of Pekanbaru. It could be seen from the result of correlation coefficient that 0,788 and significant level is 0,00<0,05. The level of correlation between moral variables with self-regulation of children.is in the middle category with the rank of determinant coefficient in the amount 62%, it means the moral intilligence principalaffect self regulation much 62% Keywords: moral intelligence,self regulation